Examining the motivation level of students in e-learning in higher education institution in Thailand: A case study - Kew, Si Na; Petsangsri, Sirirat; Ratanaolarn, Thanin; Tasir, Zaidatun (My University, 2018)
The rapid growth of Internet technology has resulted in the development of e-learning in higher education institution with the purpose of enhancing students’ performance in their learning practice. In this regard, motivation is one of the important predictors of intention to use e-learning that can in turn make impact on students’ learning practice. By knowing the motivation level of students, instructors can provide suitable teaching materials in e-learning for students to make them more engaged in e-learning activities. Nonetheless, based on the recent review studies result, there is limited research on investigating motivation level of students in e-learning in higher education institution in Thailand. Hence, this study aims to explore the motivation level of students in e-learning in higher education institutions in Thailand, using the Instructional Materials Motivation Survey and interview as the research instruments. A total of 174 students from higher education institutions in Thailand were involved in this study. SPSS software was used to analyse the data to investigate the motivation level of students, and also to compare the different motivation level of students between gender, degree level of study, branch of study and year of study. The result shows that most of the students had upper medium level of motivation level in e-learning, and there was a statistically significant difference in motivation level between the different degree levels of students. Also, the ways to enhance motivation suggested by the respondents were also discussed in this paper as a reference for the future use.
Keywords: ARCS; e-learning; Higher education institution; IMMS; Motivation level; Thailand